Dynamics of loops at the substrate entry channel determine the specificity of iridoid synthases - Sandholu, Anand S.; Mohole, Madhura; Duax, William L.; Thulasiram, Hirekodathakallu V.; Sengupta, Durba; Kulkarni, Kiran (Febs Letters, 2018)
Iridoid synthases belong to the family of short-chain dehydrogenase reductase involved in the biosynthesis of iridoids. Despite having high sequence and structural homology with progesterone 5 beta- reductase, these enzymes exhibit differential substrate specificities. Previously, two loops. L1 and L2 at substrate-binding pocket, were suggested to be involved in generating substrate specificity. However, the structural basis of specificity determinants was elusive. Here, combining sequence and structural analysis, site-directed mutagenesis, and molecular dynamics simulations, we have shown that iridoid synthase contains two channels for substrate entry whose geometries are altered by L1-L2 dynamics, primarily orchestrated by interactions of residues Glu161 and Gly162 of L1 and Asn358 of L2. A complex interplay of these interactions confer the substrate specificity to the enzyme.
Keywords: iridoid synthase; iridoids; Molecular dynamics simulations; progesterone 5 beta-reductase; Substrate specificity

Dynamic coupling analysis on plant sesquiterpene synthases provides leads for the identification of product specificity determinants - Singh, Sneha; Thulasiram, V, Hirekodathakallu; Sengupta, Durba; Kulkarni, Kiran (Biochemical and Biophysical Research Communications, 2021)
Sesquiterpene synthases catalyse cyclisation of farnesyl pyrophosphate to produce diverse sesquiterpenes. Despite utilising the same substrate and exhibiting significant sequence and structural homology, these enzymes form different products. Previous efforts were based on identifying the effect of divergent residues present at the catalytic binding pocket on the product specificity of these enzymes. However, the rationales deduced for the product specificity from these studies were not generic enough to be applicable to other phylogenetically distant members of this family. To address this problem, we have developed a novel approach combining sequence, structural and dynamical information of plant sesquiterpene synthases (SSQs) to predict product modulating residues (PMRs). We tested this approach on the SSQs with known PMRs and also on sesquisabinene synthase 1 (SaSQS1), a SSQ from Indian sandalwood. Our results show that the dynamical sectors of SSQs obtained from molecular dynamics simulation and their hydrophobicity and vicinity indices together provide leads for the identification of PMRs. The efficacy of the technique was tested on SaSQS1 using mutagenesis. To the best of our knowledge, this is a first technique of this kind which provides cues on PMRs of SSQs, with divergent phylogenetic relationship. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: molecular dynamics; Product specificity; Sesquiterpene synthases; Statistical coupling analysis; X-ray crystallography

Dishevelled2 activates WGEF via its interaction with a unique internal peptide motif of the GEF - Omble, Aishwarya; Mahajan, Shrutika; Bhoite, Ashwini; Kulkarni, Kiran (COMMUNICATIONS BIOLOGY, 2024)
The Wnt-planar cell polarity (Wnt-PCP) pathway is crucial in establishing cell polarity during development and tissue homoeostasis. This pathway is found to be dysregulated in many pathological conditions, including cancer and autoimmune disorders. The central event in Wnt-PCP pathway is the activation of Weak-similarity guanine nucleotide exchange factor (WGEF) by the adapter protein Dishevelled (Dvl). The PDZ domain of Dishevelled2 (Dvl2PDZ) binds and activates WGEF by releasing it from its autoinhibitory state. However, the actual Dvl2PDZ binding site of WGEF and the consequent activation mechanism of the GEF have remained elusive. Using biochemical and molecular dynamics studies, we show that a unique ``internal-PDZ binding motif'' (IPM) of WGEF mediates the WGEF-Dvl2PDZ interaction to activate the GEF. The residues at P 2 , P 0 , P -2 and P -3 positions of IPM play an important role in stabilizing the WGEFpep-Dvl2PDZ interaction. Furthermore, MD simulations of modelled Dvl2PDZ-WGEFIPM peptide complexes suggest that WGEF-Dvl2PDZ interaction may differ from the reported Dvl2PDZ-IPM interactions. Additionally, the apo structure of human Dvl2PDZ shows conformational dynamics different from its IPM peptide bound state, suggesting an induced fit mechanism for the Dvl2PDZ-peptide interaction. The current study provides a model for Dvl2 induced activation of WGEF. This study identifies a unique ``internal-PDZ binding motif'' (IPM) of WGEF that mediates its interaction with Dvl2PDZ, leading to the release of GEF from its autoinhibitory state. It further unravels the underlying mutual Dvl2-IPM recognition aspects.